Associations of sport participation with self-perception, exercise self-efficacy and quality of life among children and adolescents with a physical disability or chronic disease-a cross-sectional study - Saskia J. te Velde; Kristel Lankhorst; Maremka Zwinkels; Olaf Verschuren; Tim Takken; Janke de Groot; on behalf of the HAYS study group (SpringerOpen, 2018)
Abstract Background Little evidence is available about how sports participation influences psychosocial health and quality of life in children and adolescents with a disability or chronic disease. Therefore, the aim of the current study is to assess the association of sports participation with psychosocial health and with quality of life, among children and adolescents with a disability. Methods In a cross-sectional study, 195 children and adolescents with physical disabilities or chronic diseases (11% cardiovascular, 5% pulmonary, 8% metabolic, 8% musculoskeletal/orthopaedic, 52% neuromuscular and 9% immunological diseases and 1% with cancer), aged 10-19 years, completed questionnaires to assess sports participation, health-related quality of life (DCGM-37), self-perceptions and global self-worth (SPPC or SPPA) and exercise self-efficacy. Results Regression analyses showed that those who reported to participate in sports at least twice a week had more beneficial scores on the various indicators compared to their peers who did not participate in sport or less than twice a week. Those participating in sports scored better on all scales of the DCGM-37 scale, on the scales for feelings of athletic competence and children but not adolescents participating in sports reported greater social acceptance. Finally, we found a strong association between sport participation and exercise self-efficacy. Conclusions This study provides the first indications that participating in sports is beneficial for psychosocial health among children and adolescents with a disability. However, more insight is needed in the direction of the relationships.